Revisiting Online Purchase Intention in Indonesian E-Commerce: The Mediating Role of Trust and the Moderating Effect of Mobile Usability - Cheng-Wen Lee; Ahmatang Ahmatang (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This research aims to investigate the impact of e-service quality, website usability, and trust on online purchase intention among Shopee and Tokopedia users in Indonesia. A quantitative research design was applied, with the use of an online questionnaire sent to 150 respondents residing in Indonesia. Purposive sampling was employed to select individuals who have previous experiences in purchasing goods or services from Shopee and Tokopedia websites. In addition, information about their domicile was obtained to determine the respondents' geographical locations. Data analysis was performed using SPSS, incorporating validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The findings reveal that e-service quality, website usability, and trust positively and significantly impact online purchase intention in partial and simultaneous manners. Trust emerges as the strongest variable (β = 0.398), while website usability (β = 0.321) and e-service quality (β = 0.276) follow suit. The model can explain 68.1% of the variations in online purchase intention (R² = 0.681). This suggests that trust, website usability, and e-service quality are highly relevant in explaining online purchase intentions.